PENGARUH PEMERIKSAAN PAJAK, SANKSI PERPAJAKAN DAN MOTIVASI WAJIB PAJAK TERHADAP PENGGUNAAN JASA KONSULTAN PAJAK (STUDI EMPIRIS PADA KPP PRATAMA MEDAN PETISAH) - Siahaan, Christin Susanna; Sembiring, Yan Christin Br; Silalahi, Evelin Roma Riauli; Sitompul, Haryani Pratiwi (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study aims to examine the effect of tax audits, tax sanctions, and taxpayer motivation on the use of tax consultant services at KPP Pratama Medan Petisah. Given the complexity of tax regulations in Indonesia and the increasing need for professional assistance in tax matters, this study tries to understand the factors that encourage taxpayers to use tax consultant services. The research data was obtained through distributing questionnaires to individual business taxpayers registered at KPP Pratama Medan Petisah, with a sample of 100 respondents determined using the Slovin formula. Samples were taken using non-probability sampling techniques, and the results of respondents' answers were analyzed using multiple linear regression analysis techniques with the help of SPSS software version 25. The results showed that tax audits, tax sanctions, and taxpayer motivation together have a positive and significant effect on the use of tax consultant services. Partially, it was found that tax audits and tax sanctions affect the use of tax consultant services, while taxpayer motivation has no significant effect on the use of tax consultant services.